UMPAN BENUA (UNGKAPAN UCAP SYUKUR MASYARAKAT SINTANG) - Devota, Alodia; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVocabulary is one of the most important parts of learning meaning of vocabulary for second language learners, Chinese. Vocabulary includes morphemes, words, phrases and sentences. In linguistic phenomena, some morphemes and word have similar meaning. For example